1997
DOI: 10.1080/17450399709386119
|View full text |Cite
|
Sign up to set email alerts
|

Preileal digestibility of coconut fat and soybean oil in horses and their influence on metabolites of microbial origin of the proximal digestive tract1)

Abstract: Three horses (approximately 190 kg BW) fitted with a permanent fistula at the end of the jejunum were used. To a control diet (1/3 hay, 2/3 mixed feed) one of two fat types (coconut fat or soybean oil) were added at 2 levels resulting in fat intakes of 0.1 g (control diet) to 0.5 or 1 g/kg BW 0.5 d, respectively. Each experimental period consisted of 2 weeks adaptation, 2 days of breath tests (before and hourly after the morning meal) and 5 days sampling of chyme. Crude fat, crude protein, concentrations of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
3
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
9
3
1
Order By: Relevance
“…The inclusion of linseed oil did not influence this parameter by contrast to Meyer et al (1997) and Jansen et al (2002) who observed that fat supplement depressed the protein digestibility. According to Meyer et al (1997), a high fat intake may depress protein apparent digestibility in the small intestine due to a higher endogenous N-flow associated with stimulation of digestive secretions.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The inclusion of linseed oil did not influence this parameter by contrast to Meyer et al (1997) and Jansen et al (2002) who observed that fat supplement depressed the protein digestibility. According to Meyer et al (1997), a high fat intake may depress protein apparent digestibility in the small intestine due to a higher endogenous N-flow associated with stimulation of digestive secretions.…”
Section: Discussioncontrasting
confidence: 67%
“…The inclusion of linseed oil did not influence this parameter by contrast to Meyer et al (1997) and Jansen et al (2002) who observed that fat supplement depressed the protein digestibility. According to Meyer et al (1997), a high fat intake may depress protein apparent digestibility in the small intestine due to a higher endogenous N-flow associated with stimulation of digestive secretions. On the other hand and although the fact that in normal conditions the true digestibility of fat approaches 100% (Kronfeld et al, 2004), a high lipid charge in diet may increase lipid levels in the large intestine and, owing to lower caeco-colic microbial growth, decrease faecal output in microbial nitrogen (Jansen et al, 2000).…”
Section: Discussioncontrasting
confidence: 67%
“…Estimates of apparent digestibility of fat by ponies were 42 to 49% for forage and 88 to 94% of supplemented fat and oil [16]. However, Meyer et al [17] and Webb et al [18] reported no effect of diet on fat digestibility when horses were fed similar fat amounts. Digestibility differences in previous studies could be due to overall diet composition, and thus, the use of a forage-based diet was selected for this study and recommendations are made for future studies that similar considerations are made in selection of diet composition.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, measurement of breath concentrations of H2 and CH4 is useful in diagnosis of acute abdomen such as ileus or colic because it provides an effective indicator of bacterial growth. However, there have been few reports on H2 and CH4 concentrations in horse [3,6,14] because of the difficulty of measuring breath concentrations of H2 and CH4. Previously, such measurement required a large-scale measuring instrument, and thus too complicated for clinical application [2].…”
mentioning
confidence: 99%